Sustainable Amazonian Landcapes Project, SOILDATABASE Colombia - Quintero, Marcela; Romero Sánchez, Miguel Antonio; Pulleman, Mirjam Margreet; Botero Vargas, Cesar A.; Sierra, Leidi; Argote Deluque, Karolina; Suarez Salazar, Juan C.; Rodríguez Suárez, Leonardo; Rico, Adrian; Wiersma, Wietse (International Center for Tropical Agriculture, 2019)
The objective of the project is to provide national environmental authorities and local farmers in Colombia and Peru with scientific evidence to increase their capacity to mitigate and adapt to climate change, while improving environmental services and socio-economic benefits for farmers. All the parameters of the data table were evaluated in different objectives: Objective 1: Sampling of the implementations of the Conservation and Governance (C&G) and Environmentally Sustainable Milk (LAS) projects; Objective 1-2: Sampling of the implementations of the C&G and LAS projects; Objective 2: Exploratory sampling of the coverages in the two landscape units (UP4 and UP6); Objective 3: Sampling of the baseline of the SAL project implementations; Objective 3-2: Sampling of the monitoring of the SAL project implementations. (2018-06-02)